The Role of Parents and Manipulative Media in Introduction to Numbers in Early Childhood - Ellyati Farida; Novita Eka Kusuma Wardani (Jurnal MIDPRO, 2021)
ABSTRACT The concept of Numbers needs to be introduced in early childhood to help the growth and development of children in order to have readiness to enter further education. Introducing numbers in early childhood development through the role of parents and playing activities in everyday life and are natural. The purpose of this study was to analyze the influence of the role of parents and the use of manipulative media on the ability to recognize numbers in early childhood. This research was conducted in TK YKK 2 and TK Alfina and TK Al Ikhwan. The number of research samples was 109 children. The sampling technique used random sampling and cross-sectional research design. The independent variable in this study is the role of parents and the use of manipulative media, while the dependent variable is the ability to recognize the concept of numbers in early childhood. Statistical test using Rank Spearman and Logistic Regression Test. The results showed that the role of parents and the use of manipulative media together can improve the ability to recognize the concept of numbers in early childhood. The role of parents in guiding, motivating, and facilitating early childhood learning can improve children's ability to recognize numbers. The use of appropriate and interesting learning media can improve children's thinking patterns in the concept of numbers. Key words: Role of Parents; Manipulative Media; Introduction to Numbers